Linear algebra/ G. Hadley - Hadley, G. (Massachusetts: Addison-Wesley, 1961)
The text might be used in a variety of ways :for a one-semester or a one-quarter course in linear algebra;as a text or reference for part of a course in engineering mathematics , mathematical physics, or mathematical economics ;as a supplementary text for courses in linear programming; quantum mechanics, classical mechanics etc.
Introduction -- Vectors -- Matrices and Determinants -- Linear Transformations,Rank,and Elementary Transformations -- Simultaneous Linear Equations -- Convex Sets and n-Dimensional Geometry -- Characteristic Value Problems and Quadratic Forms
Includes index
Keywords: Linear Algebra